Open distance e-learning system in the institutions of higher learning in South Africa - Marutha, Ngoako Solomon; Dube, Luyanda (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
The purpose of the study was to investigate the application of open-distance e-learning systems in the institutions of higher learning to encounter pandemic and student population increase in South Africa. The in-class contact teaching and learning system can have very serious negative effects on students when it comes to a limitation of intake to universities and lockdowns in relation to outbreaks like Covid-19. This study applies the literature to develop a framework for using the open-distance electronic learning system (Open Distance e-learning – ODeL). The study discovered that institutions of higher learning, especially contact institutions, could face risks and disruptions that may result in the suspension of academic programmes. The study provides a framework for the possible adoption of the Open Distance e-learning (ODeL) system by institutions of higher learning. The results of this study will provide alert and guidance to institutions of higher learning about the adoption of open-distance e-learning to accommodate all interested students and ensure continuity of learning during a pandemic like COVID-19. The framework provided will assist institutions of higher learning with the how-to in terms of implementation of Open Distance e-learning in case they decide to adopt it. Learners will be able to get admitted and enjoy learning in any institution of their choice without any limitation due to space shortage and institutions may ensure continuity in teaching and learning for their educational business even during the pandemic.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: ODeL; Open distance education; Electronic learning; E-learning system; COVID- 19; Higher learning institutions; Computer-assisted instruction; Distance education -- Computer assisted instruction; Education, Higher; Distance education -- South Africa; Education, Higher -- South Africa